PASSENGER TRAFFIC AND FREIGHT HANDLING IN PORTS OF EUROPEAN UNION (Perner's Contacts, 2021)
This paper informs about latest statistical data of passenger traffic and freight handling in ports of European Union, covering the transport of goods between EU ports. It also presents maritime transport flows with individual results to main European ports. Information is based on data collected within the frame of the EU maritime transport statistics Directive. The content refers to the 23 of total maritime Member States.
Keywords: throughput, port, goods, cargo, passengers, European Union